Museums: Engagement and Collaboration (Cadernos de Sociomuseologia, 2014)
Until recently, plan actions in a museum was to gather content, and objects trigger a significant volume of information and collections to be exhibited for public enjoyment through exhibitions, educational activities, ultimately aimed at different public programs. Our commitment was to bring to light collections asleep in technical reserves, arrange them in an interesting way, fulfilling a chronological or thematic script, add them a lot of historical, scientific or artistic relevant information, and wait for our audience seize the entire data volume we offer them. Gradually, waves of unrest and irreverent questioning were ravaging the day to day of museums and, somehow, they were showing us that the senses should be multiple, plural. The progress of audience studies, the advent of the internet and the scope of social media, among other social and global changes of relevance, scoured the museum world so radically that it is imperative that we reflect, relax and prepare for a new time, which has now come to the museum turns into an increasingly space-forum, a territory of experiences, , shares and innovation.This text seeks to discuss some aspects of museum-forum, the museum who cares to search, to ask, to listen, to discuss, to share, to seek, to contribute to building a more just, pluralistic society, more worthy, truer, and therefore inclusive. This is the essence that should guide the museological action, committed to the reality in which the museum operates with the society  that gives it meaning, with the actions that the community elects, the practices that she recognizes as her and decides to encode and perpetuated for the future. Key words: Sharing; participation; collaboration; innovation; museology;